How to lead : wisdom from the world's greatest CEOs, founders, and game changers - Rubenstein, David M. (Simon & Schuster, 2020)
"The essential leadership playbook. Learn the principles and guiding philosophies of Bill Gates, Jeff Bezos, Ruth Bader Ginsburg, Warren Buffet, Oprah, and many others through illuminating conversations about their remarkable lives and careers"--